Chiral P,Olefin Ligands with Rotamers for Palladium-Catalyzed Asymmetric Allylic Substitution Reactions - Mino, Takashi; Yamaguchi, Daiki; Kumada, Manami; Youda, Junpei; Saito, Hironori; Tanaka, Junya; Yoshida, Yasushi; Sakamoto, Masami (Synlett, 2021)
We synthesized a series of phosphine–olefin-type chiral aminophosphines, and we confirmed that these each exists as two rotamers at the C(aryl)–N(amine) bond. We also investigated the ability of these aminophosphines to act as chiral ligands for Pd-catalyzed asymmetric allylic substitution reactions, such as the alkylation of allylic acetates with malonates or indoles, and we found they gave high enantioselectivities (up to 98% ee).
Keywords: phosphines; ligands; rotamers; asymmetric catalysis; palladium catalysis; allylic acetates